Character Education through Islamic Education: An Implementation to High School Muslim Students in North Minahasa - Abdul Latif Samal; Mustafa Mustafa; Fathum Ibrahim (STAI Hubbulwathan Duri, 2023)
This study aims to investigate the implementation of the Character Education method through Islamic Education learning for Muslim students at a senior high school in North Minahasa. The method used in this research is the descriptive qualitative method using a case study design. The researchers collected the data through observation and interviews and analyzed the obtained data through content analysis. The results of the study reported that the implementation of character education methods through Islamic Education learning for Muslim students referred to the National education goals listed in the 2013 curriculum and the Decree of the Minister of National Education Number; 54 of 2013 concerning Competency Standards for graduating elementary and secondary education. Character education can be integrated into all subjects. The implementation of character education for Muslim students at the high school in North Minahasa Regency consisted of parents’ involvement, extracurricular activities, habituation methods, exemplary, giving advice, and giving rewards and punishments.